A phased strategy to differentiate human CD14+monocytes into classically and alternatively activated macrophages and dendritic cells. (July 2016) - Zarif, Jelani C.; Hernandez, James R.; Verdone, James E.; Campbell, Scott P.; Drake, Charles G.; Pienta, Kenneth J.
There are currently several in vitro strategies to differentiate human CD14 + monocytes isolated from peripheral blood mononuclear cells (PBMCs) into the M1 or M2 macrophage cell types. Each cell type is then verified using flow cytometric analysis of cell-surface markers. Human CD14 + monocytes have the potential to differentiate into M1 and M2 macrophages, both of which demonstrate varying degrees of cell-surface antigen overlap. Using multiple surface markers with current macrophage polarization protocols, our data reveal several limitations of currently used methods, such as highly ambiguous cell types that possess cell-surface marker overlap and functional similarities. Utilizing interleukin-6 (IL-6) and two phases of cytokine exposure, we have developed a protocol to differentiate human monocytes into M1, M2, or dendritic cells (DCs) with greater efficiency and fidelity relative to macrophages and DCs that are produced by commonly used methods. This is achieved via alterations in cytokine composition, dosing, and incubation times, as well as improvements in verification methodology. Our method reliably reproduces human in vitro monocyte-derived DCs and macrophage models that will aid in better defining and understanding innate and adaptive immunity, as well as pathologic states.